Rheological Properties of Drilling Fluids: Use of Dimensionless Shear Rates in Herschel-Bulkley and Power-law Models - Saasen Arild (Applied Rheology, 2018)
An approach of Nelson and Ewoldt [1] to create a viscosity model of the Herschel-Bulkley type in order to use only parameters with the potential of containing fluid information has been extended to be applied to drilling fluids using current industry standard procedures. The commonly used Herschel-Bulkley consistency parameter k is found inadequate in describing fluid properties properly as it has a unit dependent on n. Hence, the model is not optimum for digitalisation. The Herschel-Bulkley model is re-written and base its parameters directly on the yield stress and the additional or surplus shear stress at a pre-determined shear rate relevant for the flow situation to be considered. This approach is also applicable for Power-Law models.